The Role of Musk in Relieving the Neurodegenerative Changes Induced After Exposure to Chronic Stress. Issue 4 (June 2018) - Abd El Wahab, Manal Galal; Ali, Soad Shaker; Ayuob, Nasra Naeim
Objective: This study aimed to evaluate the effect induced by musk on Alzheimer's disease—such as neurodegenerative changes in mice exposed to chronic unpredictable mild stress (CUMS). Material and Methods: Forty male Swiss albino mice were divided into 4 groups (n = 10); control, CUMS, CUMS + fluoxetine, CUMS + musk. At the end of the experiment, behavior of the mice was assessed. Serum corticosterone level, hippocampal protein level of the glucocorticoid receptors, and brain-derived neurotropic factor were also assessed. Hippocampus was histopathologically examined. Results: Musk improved depressive status induced after exposure to CUMS as evidenced by the forced swimming and open field tests and improved the short-term memory as evidenced by the elevated plus maze test. Musk reduced both corticosterone levels and the hippocampal neurodegenerative changes observed after exposure to CUMS. These improvements were comparable to those induced by fluoxetine. Conclusion: Musk alleviated the memory impairment and neurodegenerative changes induced after exposure to the chronic stress.